EXPOSING THE FALSE PARADIGM USED IN MANAGEMENT DECISION MAKING - Smith, Malan; Pretorius, Pieter (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This article discusses Economic Value Added (EVA) which is a popular shareholder value measurement. The main driving factors that influence EVA can be deduced from a modification of the Du Pont financial model. However, if these drivers are communicated to the organisation, and goals are set around achieving specific components of the drivers, the results achieved might be suboptimal. This is a direct consequence of the fact that the organisation is a system, and that EVA is an emergent property of the system. Systems theory should therefore be applied to discover the reasons for these counterintuitive outcomes in an organisation. Dilemmas (conflicts) in the system are a result of the paradigm used in understanding the system. A method to examine the conflicts that occur in a system is the three-cloud technique. By applying this technique, it is possible to find the root cause of suboptimal performance in organisations: the false underlying paradigm used in the decision making process. The incorrect paradigm is to assume that a local optimal outcome is equivalent to a global optimal outcome. AFRIKAANSE OPSOMMING: Hierdie artikel bespreek Ekonomiese Toegevoegde Waarde (ETW), 'n gewilde maatstaf van aandeel-houerwaarde. Die belangrikste drywers wat ETW beinvloed, kan afgelei word uit 'n gewysigde Du Pont model. Indien doelwitte in die organisasie rondom hierdie drywers in isolasie gestel word, kan die resultate suboptimaal wees. Die suboptimale resultate is 'n direkte gevolg van die feit dat die organisasie 'n stelsel is, en dat ETW 'n stelseleienskap is. Stelselteorie moet dus toegepas word am die onderliggende redes vir hierdie suboptimale resultate te vind. Dilemmas (konflikte) binne ' n stelsel is 'n direkte resultaat van die paradigma wat gebruik word om die stelsel te verstaan. ' n Metode om die konflikte in 'n stelsel te ondersoek is die drie-wolk metode. Deur hierdie metode toe te pas, is dit moontlik om die grondliggende oorsaak van suboptimale prestasie in 'n organisasie te vind: die foutiewe bestuursparadigma wat vir besluitneming gebruik word. Die foutiewe paradigma is om aan te neem dat 'n positiewe lokale impak van 'n besluit sal lei tot 'n positiewe globale impak.